The first case report on maturity-onset diabetes of young-11 from West Bengal, India - Manojit Sarkar (Asian Journal of Medical Sciences, 2024)
Maturity-onset diabetes of young (MODY) is a clinically group of heterogeneous disorder characterized by non-insulin-dependent diabetes diagnosed at a young age (<25 years) with autosomal dominant transmission and lack of autoantibodies. This case report is on MODY in a 30-day-old baby. The patient also has an umbilical hernia and choledochal cyst. We present an instance of 30-day-old child with MODY with a family background of diabetes. While more data are needed to justify universal screening for diabetes with tests. Practitioners should be vigilant with family history of screening of diabetes. In families two or more generations of diabetes, there should be a low threshold for asymptomatic screening with a serum Hb1Ac.